(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
The student enrolment crisis has garnered significant attention within Nepalese academic circles, policy-making bodies, and the educational sphere. Both private and public institutions of higher education, including universities, campuses, and colleges, face financial constraints due to low student enrolment rates at higher levels of education. This study recommended using a quantitative research approach to better understand how higher-level educational leaders address enrolment crises, including their perspectives, experiences, and approaches, because it is less time-consuming, can be generalised to a larger population, and reduces researchers’ bias in data collection. A structured questionnaire and a survey-based study were proposed to conduct primary research on this topic, with the latter used to collect real-world data. It is recommended that 500 higher-level administrators be randomly selected from private and public educational institutions in Chitwan, Nawalparasi, Kathmandu, Patan, Pokhara, and Bhaktapur to constitute the sample population. Furthermore, the conventional paradigm for understanding higher-level educational institutions’ enrolment crises is often narrowly focused, potentially overlooking crucial elements for effective crisis management. As a result, this study promotes a comprehensive strategy for understanding and addressing potential enrolment crises in academic environments. This research aims to improve readiness and planning mechanisms for handling student enrolment crises in higher education by expanding the conceptual framework to encompass a range of crises, including those with economic, political, or influence-related elements.